Familial cases of subacute necrotizing encephalomyelopathy (Leigh syndrome) - E.V. Shishkina; T.N. Bazilevskaya; I.V. Novikova; I.V. Leonova; Yu.G. Astanina; I.I. Cheskidova; D.A. Maiseenko (LCC «Medicine-Inform», 2021)
E.V. Shishkina1, T.N. Bazilevskaya2, I.V. Novikova2, I.V. Leonova2, Yu.G. Astanina3, I.I. Cheskidova3, D.A. Maiseenko1 1Prof. V.F. Voino-Yasenetsky Krasnoyarsk State Medical University, Krasnoyarsk, Russian Federation 2Krasnoyarsk Interregional Children's Clinical Hospital No. 1, Krasnoyarsk, Russian Federation 3I.S. Berzon Krasnoyarsk Interregional City Hospital No. 20, Krasnoyarsk, Russian Federation Mitochondrial diseases are not uncommon. However, their genetic diagnosis is challenging for practitioners and requires up-to-date high-tech methods. Early accurate diagnosis in first probands provides early preclinical genetic testing in all born children in compromised families and prenatal testing in future pregnancies, thereby allowing a differential planning of future pregnancies. This paper discusses a progressive central nervous system disorder, a congenital mitochondrial disease, subacute necrotizing encephalomyelopathy (Leigh syndrome). First, the authors briefly review etiology, prevalence, clinical presentations, diagnostic techniques, and treatment for this disease in children. Then, unique familial cases describing the diversity of clinical presentations are described. The diagnosis was genetically verified in all patients. MR signs always accompany the gradual loss of motor skills at early stages. Blood biochemistry identifies lactic acidosis. Keywords: child ren, mitochondrial diseases, subacute necrotizing encephalomyelopathy, lactic acidosis, Leigh syndrome, diagnosis, mutations in the SURF1 gene. For citation: Shishkina E.V., Bazilevskaya T.N., Novikova I.V. et al. Familial cases of subacute necrotizing encephalomyelopathy (Leigh syndrome). Russian Journal of Woman and Child Health. 2021;4(4):370-374 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-370-374.